2005
DOI: 10.1099/vir.0.81111-0
|View full text |Cite
|
Sign up to set email alerts
|

Selection of human immunodeficiency virus type 1 R5 variants with augmented replicative capacity and reduced sensitivity to entry inhibitors during severe immunodeficiency

Abstract: Early in human immunodeficiency virus 1 (HIV-1) infection CCR5-using (R5) viruses predominate. With disease progression, approximately 50 % of infected individuals develop viruses able to use CXCR4. In the present work, the evolution of the biological properties of HIV-1 was studied in patients who retain viruses with an R5 phenotype despite AIDS onset. A panel of primary R5 HIV-1 isolates sequentially obtained at an asymptomatic stage and after AIDS diagnosis was examined. The viruses were selected based on o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
49
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 52 publications
7
49
2
Order By: Relevance
“…In that study, however, the virus isolates from the acute and chronic phases of infection were obtained from different subjects. In contrast to that publication and similar to our results, other studies which have examined longitudinally collected variants have suggested that viruses become more resistant to CCR5 and fusion inhibitors over time (27,33,68). In these studies, PBMC cocultures were used to demonstrate that viruses from the chronic phase of infection have differential susceptibility to receptor and fusion inhibitors compared to late-stage variants.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In that study, however, the virus isolates from the acute and chronic phases of infection were obtained from different subjects. In contrast to that publication and similar to our results, other studies which have examined longitudinally collected variants have suggested that viruses become more resistant to CCR5 and fusion inhibitors over time (27,33,68). In these studies, PBMC cocultures were used to demonstrate that viruses from the chronic phase of infection have differential susceptibility to receptor and fusion inhibitors compared to late-stage variants.…”
Section: Discussionsupporting
confidence: 80%
“…Furthermore, TAK779 IC 50 s correlate with sensitivity to the CCR5 competitive inhibitor RANTES (Fig. 5B) (40,68). Thus, we suggest that increased CCR5 usage is because of a greater affinity for the CCR5 receptor.…”
Section: Discussionmentioning
confidence: 77%
“…R5 variants isolated from HIV-1 patients after AIDS diagnosis have reduced sensitivity to TAK-779 as compared to R5 variants isolated at the asymptomatic stage [8,9]. Strikingly, we also found a strong and significant negative correlation between HIV-2 sensitivity to MVC (as determined by the IC 50s ) and CD4 + T-cell counts at the time of virus isolation (Spearman's r=-0.831; P=0.008; Figure 1B).…”
Section: Genotypic and Phenotypic Characterization Of Virus Isolatesmentioning
confidence: 64%
“…A similar tendency was observed for TAK-779 (Additional file 3). In all, these results demonstrate that HIV-2 R5 variants have lower sensitivity to MVC than HIV-1 and suggest that resistance of these variants to MVC increases as disease progresses [8,9].…”
Section: Genotypic and Phenotypic Characterization Of Virus Isolatesmentioning
confidence: 64%
“…Patients with more advanced disease have a greater likelihood of harboring X4-utilizing viruses [52][53][54] and have R5-tropic viruses with reduced sensitivity to RANTES and the CCR5 antagonists TAK779 and AD101 compared with patients at earlier disease stages. [55][56][57][58] As a consequence, these patients may fail R5 antagonist therapy via either outgrowth of minor preexisting X4-utilizing populations or the continued use of CCR5 in the presence of drug. In patients treated earlier during the course of infection, who have lower levels of circulating X4-tropic viral isolates, continued use of R5 may be a more common resistance pathway.…”
Section: Discussionmentioning
confidence: 99%